2009
DOI: 10.1152/ajpendo.90997.2008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with SRT1720, a SIRT1 activator, ameliorates fatty liver with reduced expression of lipogenic enzymes in MSG mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an abnormal liver metabolism often observed with insulin resistance and metabolic syndrome. Calorie restriction is a useful treatment for NAFLD and reportedly prolongs the life spans of several species in which sirtuin plays an important role. In this study, we examined whether the activation of SIRT1, a mammalian ortholog of sirtuin, may ameliorate the development of NAFLD. Monosodium glutamate (MSG) mice, which exhibited obesity and insulin resistance, were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 30 publications
8
113
1
Order By: Relevance
“…We examined the effect of SRT1720 on the pulmonary metastasis of inoculated 4T1 cells as well as the size and weight of primary tumors. Our previous results showed that the oral administration of SRT1720 to normal mice did not affect body weight or food intake at a dose of 200 mg/kg over a period of 70 days (18). Therefore, SRT1720 was given at a dose of 100 mg/kg body weight.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We examined the effect of SRT1720 on the pulmonary metastasis of inoculated 4T1 cells as well as the size and weight of primary tumors. Our previous results showed that the oral administration of SRT1720 to normal mice did not affect body weight or food intake at a dose of 200 mg/kg over a period of 70 days (18). Therefore, SRT1720 was given at a dose of 100 mg/kg body weight.…”
Section: Resultsmentioning
confidence: 98%
“…The activity of SRT1720 as a SIRT1 activator is stronger than that of resveratrol. We previously reported that SRT1720 treatment decreased the expression of marker genes responsible for oxidative stress and inflammatory cytokines in the liver of monosodium glutamate (MSG)-injected ICR mice, a murine model of severe obesity and insulin resistance (18). While SIRT1 expression is upregulated in various cancers and SIRT1 inhibitors suppress cancer cell growth in vivo and in vitro, the relationship between the function of SIRT1 and cancer metastasis remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 activators might induce insulin secretion and sensitivity, reduce adipogenesis, but also induce gluconeogenesis in the liver which may worsen hyperglycemia in diabetes mellitus. Recently, Yamazaki et al [61] showed that treatment of mice with nonalcoholic fatty liver disease with a synthetic SIRT1 activator, SRT1720, might decrease the serum lipid levels, oxidative stress and inflammation. In addition, Feige et al [62] suggested that activation of SIRT1 via SRT1720 protected the organism from diet-induced obesity and insulin resistance by increasing oxidation of fatty acids in liver, adipose tissue and skeletal muscle.…”
Section: Sirtuins In Diabetes Mellitusmentioning
confidence: 99%
“…One of the compounds, sRT1720, has been shown to mitigate various negative effects of obesity and high-fat diets in both rats and mice (96)(97)(98). sRT1720 has also been shown to induce a transcriptional profile in mice reminiscent of CR, eliciting parallel changes in genes associated with mitochondrial biogenesis, metabolic signaling, and inflammatory pathways (99).…”
Section: Sirtuin Activatorsmentioning
confidence: 99%